E-Learning for Sport Science Education: Importance and Mapping Analysis through a Big-Scale Survey - Indrayana, Boy; Sukendro , Sukendro; Widowati , Atri; Nugraha , Ugi; Melansari , Nur; Yandra, Alexsander (Utamax : Journal of Ultimate Research and Trends in Education, 2024)
In the evolving landscape of sports science education, the integration of e-learning has become a pivotal element for enhancing the educational experience. This study aims to dissect the impact of various external factors, including the use of social media, perceived usefulness, perceived ease of use, playfulness, attitude towards use, and intention to use, on the adoption of e-learning among sports students. Employing a quantitative research design, this cross-sectional survey engaged 922 active sports education students from a total pool of 1,072, using a comprehensive questionnaire to gather data. The Partial Least Squares Structural Equation Modeling (PLS-SEM) was utilized for hypothesis testing and data analysis, focusing on instrument quality, data normality, and analysis model quality. The findings illuminate the significant influence of social media usage on the perceived ease of use and usefulness of e-learning, validating nine out of eleven hypotheses. A novel discovery of this research is the elucidation of social learning effects, indicating that sports students, who are frequent users of social media platforms like WhatsApp, Facebook, and Instagram, exhibit enhanced familiarity and interaction with digital technology, facilitating their mastery and understanding of e-learning platforms. Furthermore, the study underscores the role of social media as a supportive tool for information exchange and overcoming e-learning challenges among peers. Implications of this study are manifold, offering valuable insights for educational institutions and policy-makers to leverage social media in promoting e-learning adoption, focusing on improving usability and accessibility for students. This research contributes to the broader discourse on e-learning in sports science education, providing a foundation for future explorations into the integration of technology in educational practices.